Corporate Social Responsibility (CSR): Motivations and challenges of a Multinational Enterprise (MNE) subsidiary's engagement with host communities in Ghana - Lyon Salia Awuah; Kwame Oduro Amoako; Stephen Yeboah; Emmanuel Opoku Marfo; Peter Ansu-Mensah (International Journal of Corporate Social Responsibility (JCSR), 2021)
This paper aims to explore the motivations and challenges of engaging host communities in CSR practices within the context of Newmont Ahafo Mines (NAM), a subsidiary of a Multinational Mining Enterprise (MNE) operating in Ghana's mining sector. This paper draws insights from stakeholder theory and interviews conducted with internal stakeholders (management and employees) and stakeholders in host communities (traditional rulers and community members). The findings indicate that effective decision-making, gaining legitimacy, cost savings, management of risks, and accountability are some of the perceived motivations of NAM's stakeholder engagement in CSR. Nonetheless, the most critical challenges to NAM in improving stakeholder engagement in CSR practices are the lack of community members' support in CSR projects, communities' high expectations of NAM on development projects and over-dependency on NAM on the part of host communities. Therefore, it is reasonable for MNEs in emerging economies to attune engagement practices to the host community's context. This will enable CSR practices and policies to fully exploit the latent benefits of CSR in the mining sector.
Keywords: 650; Corporate social responsibility; Emerging economies; Stakeholder engagement; Motivations; challenges